An Empirical Analysis of SME Finance in Turkey: Identifying the Macroeconomic and Firm Specific Factors Affecting SMEs’ Access to Finance - Hossain, Md Monir (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This thesis provides an empirical analysis of SMEs‘ access to financial services and credit in Turkey. It identifies the macroeconomic factors that affect banks‘ credit supply decisions to SMEs, and the firm-specific factors that determine SMEs‘ demand for bank credit and financial services. The macroeconomic, i.e. the supply-side analysis confirmed the conceptual hypothesis that banks‘ lending to SMEs is fuelled by economic growth and stability, financial market efficiency and banking competition, but hampered by the extent of government borrowing from domestic creditors. The firm-level analysis provided evidence that in recent years, SMEs in Turkey found it easier to access bank loans. Evidently, according to the 2015 WBES survey in Turkey, the rejection rate for bank credit was as low as 7% and only 16% of SMEs had cited access to credit as a major obstacle. Although these statistics are valid for the whole Turkish economy, this research discovered that there are significant regional discrepancies in the usage of credit and non-credit financial services in Turkey. In less developed regions, only a small percentage of SMEs have bank accounts, and use bank credit for financing working capital. Yet, it is also found that in these regions, SMEs mostly rely on bank loans for financing their fixed assets. Regarding to firm specific factors it is found that SMEs‘ size, operating performance as well as business ownership type and managerial competency (e.g. education level, business experience) are significant determinants for the demand for formal financial services in Turkey. Keywords: SME finance, credit supply, credit demand, macroeconomic factors, firm‘s specific factors, OLS & GLMs regression.

ÖZ: Bu tez, Türkiye‘de KOBİ'lerin finansal hizmetlere ve kredilere erişiminin ampirik bir analizini sunmaktadır. Bankaların KOBİ'lere kredi tedarik kararlarını etkileyen makroekonomik faktörleri ve KOBİ'lerin banka kredisi ve finansal hizmetler için talebini belirleyen firmalara özgü faktörleri belirler. Makroekonomik, yani arz-taraf analizi, bankaların KOBİ'lere borç vermesinin ekonomik büyüme ve istikrar, finansal piyasa etkinliği ve rekabet gücü ile körüklendiği, fakat devletin iç borçlanması ile zayıflatıldığını göstermiştir. Öte yandan, firma düzeyinde yaptığımız analiz, son yıllarda, Türkiye'deki KOBİ'lerin banka kredilerine daha kolay eriştiğini kanıtlamıştır. Açıkça, 2015 yılında yapılan WBES anketine göre banka kredisi için red oranı% 7 gibi düşük bir orana sahipti ve KOBİ'lerin sadece% 16'sı kredi erişimini önemli bir engel olarak göstermişti. Bu istatistikler tüm Türkiye ekonomisi için geçerli olmakla birlikte, bu araştırma Türkiye'de kredi ve kredi dışı finansal hizmetlerin kullanımında önemli bölgesel farklılıklar olduğunu ortaya çıkarmıştır. Daha az gelişmiş bölgelerde, KOBİ'lerin sadece çok küçük bir yüzdesi banka hesaplarına sahiptir ve işletme sermayesini finanse etmek için banka kredisi kullanmaktadır. Yine de, bu bölgelerde KOBİ'lerin çoğunlukla sabit varlıklarını finanse etmek için banka kredilerine başvurdukları da görülmektedir. KOBİ‘lerin krediye erişiminde sirkete özgü faktörlere bakarsak, KOBİ'lerin performansının yanı sıra KOBİ sahiplerinin eğitim seviyesi ve yönetim yeterliliğinin Türkiye'deki banka kredilerine ve finansal hizmetlere olan talebin önemli belirleyicileri olduğu görülmektedir. Anahtar Kelimeler: KOBİ finansmanı, kredi arzı, kredi talebi, makroekonomik faktörler, firmanın spesifik faktörleri, OLS ve GLMs regresyonu.
Doctor of Philosophy in Finance. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2019. Supervisor: Prof. Dr. Hatice Jenkins.
Keywords: Banking and Finance; Small and Medium Size Enterprises--Turkey; SME finance; credit supply; credit demand; macroeconomic factors; firm‘s specific factors; OLS & GLMs regression